Gonadotropin-releasing hormone agonist triggering of oocyte maturation in assisted reproductive technology cycles - Türkgeldi, Engin (Turk J Obstet Gynecol, 2015)
Gonadotropin-releasing hormone agonists (GnRHa) have gained increasing attention in the last decade as an alternative trigger for oocyte maturation in patients at high risk for ovarian hyperstimulation syndrome (OHSS). They provide a short luteinizing hormone (LH) peak that limits the production of vascular endothelial growth factor, which is the key mediator leading to increased vascular permeability, the hallmark of OHSS. Initial studies showed similar oocyte yield and embryo quality compared with conventional human chorionic gonadotropin (hCG) triggering; however, lower pregnancy rates and higher miscarriage rates were alarming in GnRHa triggered groups. Therefore, two approaches have been implemented to rescue the luteal phase in fresh transfers. Intensive luteal phase support (iLPS) involves administiration of high doses of progesterone and estrogen and active patient monitoring. iLPS has been shown to provide satisfactory fertilization and clinical pregnancy rates, and to be especially useful in patients with high endogenous LH levels, such as in polycystic ovary syndrome. The other method for luteal phase rescue is low-dose hCG administiration 35 hours after GnRHa trigger. Likewise, this method results in statistically similar ongoing pregnancy rates (although slightly lower than) to those of hCG triggered cycles. GnRHa triggering decreased OHSS rates dramatically, however, none of the rescue methods prevent OHSS totally. Cases were reported even in patients who underwent cryopreservation and did not receive hCG. GnRH triggering induces a follicle stimulating hormone (FSH) surge, similar to natural cycles. Its possible benefits have been investigated and dual triggering, GnRHa trigger accompanied by a simultaneous low-dose hCG injection, has produced promising results that urge further exploration. Last of all, GnRHa triggering is useful in fertility preservation cycles in patients with hormone sensitive tumors. In conclusion, GnRHa triggering accompanied by appropriate luteal phase rescue protocols is a relatively safe option for patients at high risk for OHSS.